DIFFERENT PERSPECTIVES ON AESTHETIC EDUCATION NOWADAYS - Calmon Nabuco Lastoria, Luiz Antonio [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
The reference to human sensibility, to the dimension of the sensible as the object of education itself; finds its most distant formulation in Plato's Republic. However, this task has remained a problem lacking a reasonable equation until now. In Brazil, especially after the publication of the National Curriculum Parameters in 1997, the discussions and propositions for an education of the sensibility have intensified. Our purpose, considering the limits of this paper consists in the exposition and reflection of two different theoretical perspectives. They are situated in different historical moments of the twentieth century and they are important reference for the national debate regarding a supposedly education of sensibility nowadays. This is the case of Soviet psychologist and theorist Lev S. Vygotsky (1896) and of the French philosopher Jacques Ranciere (1940).
Keywords: Esthetics education; Civilization; Contemporary